Empirical study of sukuk investment forecasting using artificial neural network base algorithm - Nurul Hila binti Zainuddin (Tanjong Malim, 2019)
Empirical study of sukuk investment forecasting using artificial neural network base algorithm by Nurul Hila binti Zainuddin